(untitled) (Journal of Bangladesh Academy of Sciences, 2025)
Elevated bicarbonate (HCO₃⁻) concentrations in natural waters can promote phosphate (PO4) release from the bottom sediments to the overlying water. However, the chemical processes driving this bicarbonate-induced release at the sediment-water interface are not well understood. This study examines how HCO3- and calcium (Ca2+) affect PO4 adsorption to ferric (hydr)oxide under static and dynamic pH conditions. Results show that HCO3- competes with PO4 for the surface binding sites, reducing PO4 adsorption under static pH conditions. In contrast, Ca2+ enhances PO4 adsorption, particularly under alkaline conditions. For instance, at pH 8, the presence of 0.25 mM HCO3- reduced PO4 adsorption, as reflected by a Kd value (the ratio of aqueous to solid-phase PO4) that was 1.7 times higher than the Kd value of 0.39 observed in a solution containing only 10 mM NaCl. This competitive effect of HCO3- on PO4 adsorption diminishes significantly when Ca2+ is simultaneously present. For example, the Kd value of PO4 at pH 8 in the presence of HCO3- alone is 0.66, but decreases to 0.55, 0.37, and 0.24 with the addition of 0.05, 0.1, and 0.25mM Ca2+, respectively. A similar trend was observed in adsorption experiments conducted under dynamic pH conditions. However, the Kd value in dynamic pH experiments was approximately 84% lower than in static pH conditions, suggesting that PO4 became immobilized on solid surfaces, likely due to the formation of stronger surface complexes over time. These results imply that high concentrations of HCO3- may increase PO4 mobility in the water column by limiting PO4 adsorption from the aqueous phase, rather than by enhancing its desorption from sediment surfaces. J. Bangladesh Acad. Sci. 49(1); 137-146: June 2025